An Analysis of Inflation Growth and Economic Growth in Indonesia, 2019–2024 - Hotma Mentalita; Jenni Veronika Br Ginting; Fitra Tur Radiyah; Tri Dessy Ratna Sari (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The purpose of this study is to investigate how Indonesian inflation and its economic growth. The research period of 2019–2024 is particularly significant because it includes dramatic macroeconomic oscillations caused by COVID-19 pandemic and the following economic recovery phase. This research uses official statistical sources of Indonesia to provide secondary time-series data. Adopting a quantitative exporal approach, inflation growth is considered the independent variable and economic growth serves as its dependent metric. We analyze the data using descriptive statistics and regression analysis to see the size and direction of relationship between our two alternating variables. The results showed that inflation growth has a significant effect on economic growth, because the period of research in both price stability and output performance in Indonesia reflects this dynamic interaction. These findings suggest that when handled properly, inflationary pressures do not necessarily impede economic growth. Conversely, they may be a reflection of ongoing economic adjustments in grave of the pandemic. This paper adds to macro-economic literature by presenting new empirical evidence using data from Indonesia since 1983 and looking at inflation growth rather than just the level of inflation. Policy implications for this result are that relevant bits of data help decision-makers keep macroeconomic stability while fostering sustainable economic growth.